1988
DOI: 10.12938/bifidus1982.7.2_71
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Candida Overgrowth and Candida Infection in Patients with Leukemia: Effect of Bifidobacterium Administration

Abstract: The number of intestinal Candida was correlated with the incidence of Candida infection. The number of intestinal Candida was higher in patients receiving antileukemic chemotherapy than in normal subjects. Respiratory and urinary infections were increased in patients with more than 105 Candida/g feces. Bifidobacterium administered orally to patients with more than 105 Candida/g feces, reduced the incidence of infection if the intestinal Candida population fell to less than 104/g feces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Side effects were ameliorated by the administration of probiotic bacteria before and during chemo- (80) or radiotherapy (81,82).…”
Section: Diarrhea In Immunocompromised Subjectsmentioning
confidence: 99%
“…Side effects were ameliorated by the administration of probiotic bacteria before and during chemo- (80) or radiotherapy (81,82).…”
Section: Diarrhea In Immunocompromised Subjectsmentioning
confidence: 99%
“…Antibiotic-associated overgrowth of Candida species in the gastrointestinal tract may have important clinical implications. Tomoda et al (14) found that leukemia patients with Ն10…”
mentioning
confidence: 99%
“…Like the EB virus and Aspergillus infection through respiratory tract (13,14), urinary tract infection caused by Escherichia coli (15) and derma infection is caused by Herpes Zoster (16). However, infection caused by intestinal microbiology is rare, just a report of intestinal dysbacteriosis (17). As Chun-Ru Hsu et al (18) reported K. pneumoniae can translocate across the intestinal epithelium; the gut is always the epicentre of antibiotics resistance (19).…”
Section: Discussionmentioning
confidence: 99%